Macrophage-driven immunopathology in pulmonary arterial hypertension: from mechanisms to targeted therapies - Xu, Wenna; Shen, Yunlong; Wan, Zhengdong; Guo, Jiawei (Frontiers in Immunology, 2025)
Pulmonary arterial hypertension (PAH) is a progressive vascular disorder characterized by obstructive vascular remodeling driven by the aberrant proliferation of endothelial cells, smooth muscle cells, and adventitial fibroblasts within the small pulmonary arteries. Emerging evidence highlights a pivotal role for macrophage polarization in PAH pathogenesis. In the pulmonary vasculature, macrophages drive local inflammation and fibrosis through M1/M2 polarization, while the inflammatory mediators they release can also alter the systemic immune environment and indirectly influence right ventricular remodeling through the “lung–heart immune axis.” This phenotypic plasticity is tightly governed by hypoxia-induced signaling pathways, metabolic reprogramming, and epigenetic modifications. Elucidating these mechanisms has revealed macrophage polarization and immunometabolic regulation as promising therapeutic targets for PAH. Future investigations focusing on macrophage heterogeneity, single-cell transcriptomics, and precision immunomodulatory strategies are expected to accelerate the development of targeted therapies and improve clinical outcomes in PAH.